Human Resource Planning and Organizational Performance: A Case Study of Finn Church Aid Uganda - Joyce Eimani (Uganda Christian University, 2023)
The study was about human resource planning and organizational performance. A case study of Finn church Aids Adjumani. The objectives of the study were, to examine the nature of human resource planning on organizational performance, to find out factors affecting human resource planning on organizational performance, to assess the relationship between human resources planning on organizational performance. The problem of the study was the looming challenges some organization in Uganda are facing in attracting and retaining skilled and valuable employees to meet service delivery need. The research target a population of so employees of Finn church aids among who were randomly selected according to the department which included the Administration, finance department, information technology and marketing department. The study adapted a descriptive research design which involve surveying people and recording their responses for analysis within the descriptive design. The study also incorporated both qualitative and quantitative approaches to understand better the relationship between variables in the research problem. The cross sectional research was used to help collect views of sample population at a single point of time. The research finding was that human resource planning have a great effect on the performance of the organization. The finding also showed that competitive advantage can be obtain by proper recruitment and selection (fadare,2015) puts it a cross that for organization to gain competitive advantage, they should devise a strategy to carefully recruit and select the most that the training design of the organization is in accordance to the need of employees which enable them to perform better. The finding showed that training and development increase the overall performance of the organization about this is in agreement with Shepard 2003.the study findings further showed. The finding show that regarding the organizations practice of conducting regular workforce analysis to identify skill gap and talent requirements reflects a proactive approach to address skill shortage. This approach could contribute to maintaining a competitive workforce and ensuring that organization has the right talent to achieve its objective. The finding further states that the overwhelmingly positive response (90%) about employees being satisfied with opportunity for career advancement and goal achievement is promising sign. This suggests that the organization is providing a conducive environment for career growth, which can enhance employee motivation and retention. The recommendation to the organization were the organization should address concerns related to collaboration across department, diverse and inclusion effects and potentially varying levels of employee engagement which in long run can contribute to enhancing organizational effectiveness ,employee satisfaction and overall performance. The organization should address the issues of work life balance, employee engagement through clear communication, employee engagement initiative and effective recruitment strategies that in the long run could help the organization align its practices with employee expectations and contribute to improved organizational performance. The organization should invest in other human resource planning methods that have a high effect on the performance of the organization and also prioritize succession planning so as to be more effective to the organization.
This is a dissertation.